2008
DOI: 10.1016/j.febslet.2008.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of U24 from Human Herpes Virus type 6 (HHV‐6) and its potential role in mimicking myelin basic protein (MBP) in multiple sclerosis

Abstract: Myelin basic protein (MBP) from multiple sclerosis (MS) patients contains lower levels of phosphorylation at Thr97 than normal individuals. The significance of phosphorylation at this site is not fully understood, but it is proposed to play a role in the normal functioning of MBP. Human Herpesvirus Type 6 encodes the protein U24, which has tentatively been implicated in the pathology of MS. U24 shares a 7 amino acid stretch encompassing the Thr97 phosphorylation site of MBP: PRTPPPS. We demonstrate using a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
0
27
0
1
Order By: Relevance
“…ICP27 is involved in a series of processes in the nucleus and the cytoplasm, where it is attributed to a number of different protein interactions. Host protein-protein interactions are often regulated by phosphorylation, and phosphorylation events are reported to regulate a number of herpesvirus proteins (39)(40)(41)(42)(43). ICP27 is observed to have both stable and transient phosphorylations (44).…”
Section: Resultsmentioning
confidence: 99%
“…ICP27 is involved in a series of processes in the nucleus and the cytoplasm, where it is attributed to a number of different protein interactions. Host protein-protein interactions are often regulated by phosphorylation, and phosphorylation events are reported to regulate a number of herpesvirus proteins (39)(40)(41)(42)(43). ICP27 is observed to have both stable and transient phosphorylations (44).…”
Section: Resultsmentioning
confidence: 99%
“…This was associated with febrile illness, delayed transplant engraftment, and neurological involvement, up to lethal encephalitis (5,13,34,46). HHV-6A has thus far no clear disease association, although several studies have suggested central nervous system (CNS) tropism, including aggravation of symptoms in patients with multiple sclerosis (MS) (6,14,33,41).…”
mentioning
confidence: 99%
“…The extent of phosphorylation of U24, however, is much weaker than that of MBP. 6 Here we find that a binding interaction between U24 and Fyn-SH3 exists, but it is again most likely much weaker than the interaction between MBP and Fyn-SH3. Although a K D value was never reported for MBP/Fyn-SH3, a crude estimate based on the data reported in ref 15 can be made (K D ≈ 0.1−1 mM).…”
Section: ■ Discussionmentioning
confidence: 93%
“…6,20 The mass of the isolated mutant NΔ9-U24 protein was obtained by matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry, which confirmed that the protein had the desired mutation, having an N-terminal sequence of nine amino acids Figure 1. Sequences of MBP (residues 89−103, numbering used to correspond to numbering in the murine classic 18.5 kDa MBP isoform 17 ), U24 from HHV-6A (residues 1−15), and U24 from HHV-7 (residues 1−15).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%